Identity and Belonging: Exploring the Multifaceted Journey in Maryse Conde's Novels (International Journal of Food and Nutritional Sciences, 2022)
French novelist and critic, Maryse Conde was born in Guadeloupe in the year 1937 and has contributed a lot to contemporary literature, for her literary contributions she was awarded the Alternative Nobel prize in literature in the year 2018. Conde explores the themes of identity and belonging in many of her novels. This article explores the multifaceted nature of identity by examining the perilous journeys undertaken by Conde’s characters due to many socio-political and economic factors. The analysis delves into socio-political factors like Colonialism and slavery, which exploited millions of Africans by displacing them to foreign lands. The experiences of the displaced individuals are studied to highlight the factors that lead to identity crises. The internal and external factors that influence an individual's sense of self and belonging are explored within the context of Conde’s narratives. The importance of culture and the impact of cultural clashes in constructing an individual’s sense of self are also explored. The intricate nature of an individual's identity and its relationship with the culture and society are explored, with a particular focus on the importance of one’s sense of belonging.